Evaluasi Program Sertifikasi Kompetensi Kerja Keahlian OTKP SMK Negeri 45 Jakarta - Pramesthi Khairunnisa Aulia pramesthi; Musringudin musringudin (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
SMK Negeri 45 Jakarta is one that already has a First Professional Certification Institute or LSP - P1 as evidenced by the license from BNSP. The First Professional Certification Body or LSP, is very important in issuing Work Competency Certification. Certification of Work Competence is what will affect the results of students in the future. This study aims to evaluate the KKNI level II work competency certification program for students of office automation and governance expertise. This research was conducted at SMK Negeri 45 Jakarta. This research uses descriptive qualitative research methods with the CIPP Evaluation Method. The CIPP method focuses on Context, namely the legal basis, vision and mission and objectives, Input, namely students, educators, facilities and infrastructure, financing, curriculum and assessors, Process, namely registration, pre-assessment, and assessment and Product includes reporting results. This program has a positive impact on the skills of work competency certification participants at SMK Negeri 45 Jakarta.